Reduction of Dietary Fat Rescues High-Fat Diet-Induced Depressive Phenotypes and the Associated Hippocampal Astrocytic Deficits in Mice - Kai-Pi Cheng; Hsin-Hao Chao; Chin-Ju Hsu; Sheng-Feng Tsai; Yen-Ju Chiu; Yu-Min Kuo; Yun-Wen Chen (Metabolites)
Background/Objectives: Depression is frequently comorbid with obesity. We previously showed that astrocyte-mediated hyperactive ventral hippocampal glutamatergic afferents to the nucleus accumbens determined the exhibition of depression-like behaviors in obese murine models. However, it remains unclear if the metabolic disorder-induced depressive phenotypes and astrocytic maladaptation in the ventral hippocampus (vHPC) could be reversed following the amelioration of key metabolic impairments such as insulin resistance and dyslipidemia. Method: Male mice were fed a high-fat diet (HFD) for 12 weeks, followed by either continued HFD feeding (HFD/HFD group) or a switch to a standard diet for 4 weeks (HFD/SD group). Results: Results showed that HFD/HFD mice displayed not only glucose/lipid metabolic dysfunction, but also depression-like behaviors. In contrast, HFD/SD mice showed improvements in metabolic disorders and depressive phenotypes. Mechanistically, dietary fat reduction restored astrocyte morphology and glutamate transporter expression (GLT-1, GLAST) in the vHPC and suppressed neuroinflammatory signaling, as evidenced by reduced levels of phospho-IKK, TNF-α, IL-1β, and IL-6 in the vHPC. Conclusions: These findings suggest that dietary fat reduction reverses obesity-induced depressive phenotypes, astrocytic deficits, at least in part via suppression of neuroinflammation through the NF-κB signaling pathway.